Calcitriol exerts an anti‐tumor effect in osteosarcoma by inducing the endoplasmic reticulum stress response. Issue 9 (16th July 2017) - Shimizu, Takatsune; Kamel, Walied A.; Yamaguchi‐Iwai, Sayaka; Fukuchi, Yumi; Muto, Akihiro; Saya, Hideyuki
Abstract : Osteosarcoma is the most common type of primary bone tumor, and novel therapeutic approaches for this disease are urgently required. To identify effective agents, we screened a panel of Food and Drug Administration (FDA)‐approved drugs in AXT cells, our newly established mouse osteosarcoma line, and identified calcitriol as a candidate compound with therapeutic efficacy for this disease. Calcitriol inhibited cell proliferation in AXT cells by blocking cell cycle progression. From a mechanistic standpoint, calcitriol induced endoplasmic reticulum (ER) stress, which was potentially responsible for downregulation of cyclin D1, activation of p38 MAPK, and intracellular production of reactive oxygen species (ROS). Knockdown of Atf4 or Ddit3 restored cell viability after calcitriol treatment, indicating that the ER stress response was indeed responsible for the anti‐proliferative effect in AXT cells. Notably, the ER stress response was induced to a lesser extent in human osteosarcoma than in AXT cells, consistent with the weaker suppressive effect on cell growth in the human cells. Thus, the magnitude of ER stress induced by calcitriol might be an index of its anti‐osteosarcoma effect. Although mice treated with calcitriol exhibited weight loss and elevated serum calcium levels, a single dose was sufficient to decrease osteosarcoma tumor size in vivo . Our findings suggest that calcitriol holds therapeutic potential for treatment of osteosarcoma, assuming that techniques to diminish its toxicity could be established. In addition, our results show that calcitriol could still be safely administered to osteosarcoma patients for its original purposes, including treatment of osteoporosis. Abstract : Anti‐tumor effect of calcitriol in osteosarcoma by inducing the ER stress response.